Application Programs for Learning Arabic in the Industrial Era 4.0: A Qualitative Analysis of Teachers and Students in Aceh - Sullati Armawi; Afrah Masood (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2024)
This article describes learning Arabic using online applications in secondary and tertiary schools in the Aceh region. It analyzes the benefits and obstacles faced by teachers and students. This research uses the qualitative-analytical approach using Creswell's analysis theory, including data preparation and processing, building a general sense of information, and coding and interpreting the data. This research shows that learning the Arabic language through online applications is an activity that provides information, especially Arabic language studies, through the Internet, such as via WhatsApp, Google Classroom, Zoom, Kahoot, and Quizizz applications. Using these applications makes them more knowledgeable in developing their technology capabilities. Technology can accustom students to independent learning and not rely on the teacher's explanation alone, creating the habit of reading and analyzing educational materials. One of the obstacles to learning through electronic media is the lack of access to the Internet in rural areas of Aceh. There are no computers or laptops for students, and there are materials that are difficult to understand.